Avifaunal Diversity, Conservation Status, and Ecological Roles in Production Forests of Aceh Besar Regency - T. Dedi Kiswayadi; Eka Sriwulandari; Bakruddin Bakruddin (Information Technology and Science (ITScience), 2026)
Birds (avifauna) play an essential role in maintaining ecosystem balance as seed dispersers, insect predators, and pollinators. However, anthropogenic pressures in production forests threaten their habitats, including in Aceh Besar Regency. This study aims to assess avifaunal diversity, conservation status, and ecological roles in production forest areas. This study was conducted in Kota Jantho, Kuta Cot Glie, and Seulimum at elevations ranging from 250 to 1,700 meters above sea level. Observations were carried out using the line transect method across 10 transects (30 plots, 50 × 50 m). Avifaunal diversity was analyzed using the Shannon–Wiener diversity index (H’), while conservation status referred to the IUCN Red List (2025) and Indonesian regulation (Permen LHK No. P.106/2018). The results recorded 26 bird species, consisting of 22 species categorized as Least Concern (LC) and 1 species as Vulnerable (VU), while 3 species are listed as nationally protected. The diversity index indicated a moderate level of diversity. The presence of frugivorous, insectivorous, and nectarivorous birds highlights their ecological roles in forest regeneration, pest control, and pollination. Lower species richness compared to conservation areas is likely associated with habitat fragmentation and anthropogenic pressures such as shifting cultivation and illegal logging. These findings indicate that production forests still function as important habitats, although they are under ecological pressure. Conservation strategies should include community-based monitoring, biodiversity-based spatial planning, law enforcement, and environmental education.